Differentiating central nervous system demyelinating disorders: The role of clinical, laboratory, imaging characteristics and peripheral blood type I interferon activity - Karathanasis, Dimitris K.; Rapti, Anna; Nezos, Adrianos; Skarlis, Charalampos; Kilidireas, Constantinos; Mavragani, Clio P.; Evangelopoulos, Maria Eleftheria (Frontiers in Pharmacology, 2022)
While multiple sclerosis (MS) is considered the cornerstone of autoimmune demyelinating CNS disorders, systemic autoimmune diseases (SADs) are important MS mimickers. We sought to explore whether distinct clinical, laboratory and imaging characteristics along with quantitation of peripheral blood type I interferon (IFN) activity could aid in differentiating between them. 193 consecutive patients with imaging features suggesting the presence of CNS demyelinating disease with or without relevant clinical manifestations underwent full clinical, laboratory and imaging evaluation, including testing for specific antibodies against 15 cellular antigens. Expression analysis of type I IFN-inducible genes (MX-1, IFIT-1, IFI44) was performed by real time PCR and a type I IFN score, reflecting type I IFN peripheral activity, was calculated. After joint neurological/rheumatological evaluation and 1 year of follow-up, patients were classified into MS spectrum and CNS autoimmune disorders. While 66.3% (n=128) of the patients were diagnosed with MS spectrum disorders (predominantly relapsing-remitting MS), 24.9% (n=48) were included in the CNS autoimmune group and out of those, one fourth met criteria for SAD (6.7% of the cohort, n=13); the rest (18.1% of the cohort, n=35), despite showing evidence of systemic autoimmunity, did not fulfill SAD criteria and comprised the “demyelinating disease with autoimmune features” (DAF) subgroup. Compared to MS spectrum, CNS autoimmune patients were older, more frequently females, with increased rates of hypertension/hyperlipidemia, family history of autoimmunity, cortical dysfunction, anti-nuclear antibody titers ≥1/320, anticardiolipin IgM positivity and atypical for MS magnetic resonance imaging lesions. Conversely, lower rates of infratentorial and callosal MRI lesions, CSF T2 oligoclonal bands and IgG-index positivity were observed in CNS autoimmune patients. Patients fulfilling SAD criteria, but not DAF group, had significantly higher peripheral blood type I IFN scores at baseline compared to MS spectrum [median (IQR)]: 50.18 (152.50) vs -0.64 (6.75), p-value: 0.0001. Our study suggests that underlying systemic autoimmunity is not uncommon in patients evaluated for possible CNS demyelination. Distinct clinical, imaging and laboratory characteristics can aid in early differentiation between MS and CNS-involving systemic autoimmunity allowing for optimal therapeutic strategies. Activated type I IFN pathway could represent a key mediator among MS-like-presenting SADs and therefore a potential therapeutic target.